1983
DOI: 10.1152/ajpregu.1983.245.5.r689
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base and ionic balance in Ambystoma tigrinum and Necturus maculosus during hypercapnia

Abstract: The aquatic urodeles Ambystoma tigrinum and Necturus maculosus responded to hypercapnia quite differently. A. tigrinum, after 2-h exposure to 22 Torr partial pressure of CO2 (PCO2), decreased arterial pH (pHa) from 7.85 to 7.32 and increased arterial pressure of CO2 (PaCO2) to 26 Torr. Plasma [HCO-3] [( HCO-3]pl) remained constant at about 17 mM. Prolonged exposure (24 h) led to a 26% extracellular compensation as pHa rose to 7.46 while [HCO-3]pl increased to 24 mM. Plasma [K+] increased and [Cl-] decreased wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Compensation to a respiratory acidosis can be calculated as (Siesjo, 1971); the resultant percentage is the recovery of pH relative to its value at the increased P CO 2 if there were no change in []. For N. maculosus in the Stiffler et al (1983) study, compensation is 11%, low in comparison to similar calculations for Ambystoma tigrinum larvae (26–43%), and C. alleganiensis (40%) faced with a similar degree of environmental hypercarbia (Ultsch, 1996). Whether N. maculosus defends intracellular pH while essentially abandoning compensation of plasma pH, as in S. lacertina and A. means (see ) is not known.…”
Section: Species Accountscontrasting
confidence: 56%
See 1 more Smart Citation
“…Compensation to a respiratory acidosis can be calculated as (Siesjo, 1971); the resultant percentage is the recovery of pH relative to its value at the increased P CO 2 if there were no change in []. For N. maculosus in the Stiffler et al (1983) study, compensation is 11%, low in comparison to similar calculations for Ambystoma tigrinum larvae (26–43%), and C. alleganiensis (40%) faced with a similar degree of environmental hypercarbia (Ultsch, 1996). Whether N. maculosus defends intracellular pH while essentially abandoning compensation of plasma pH, as in S. lacertina and A. means (see ) is not known.…”
Section: Species Accountscontrasting
confidence: 56%
“…5; Ultsch, 1971, 1973 b , 1996). Stiffler, Tufts & Toews (1983) reported that when N. maculosus were exposed to a water P CO 2 ( P w CO 2 ) of 17.3 mmHg at 25 o C, there was little compensation of extracellular pH after 24 h, P a CO 2 rose from 7.0 to 24.5 mmHg, and there were no changes in plasma strong ion concentrations. Compensation to a respiratory acidosis can be calculated as (Siesjo, 1971); the resultant percentage is the recovery of pH relative to its value at the increased P CO 2 if there were no change in [].…”
Section: Species Accountsmentioning
confidence: 99%
“…During acute exposure to hypercarbia, purely aquatic vertebrates such as trout can rapidly raise and maintain their [HCO,-jlevels (Janssen and Randall, 1975;Thomas, 1983;Thomas and Le Ruz, 1982). On the contrary, Stiffler et al (1983) found that TABLE 1. Particularly instructive are the values for the four species of North American giant salamanders.…”
Section: An Alternative Theory: the Effects Of Hypercarbia On Aquaticmentioning
confidence: 99%
“…An incision was made on the ventral surface of the animal anterior to the sternum. A nonocclusive polyethylene (PE 50) cannula, containing 125 units heparinlmL and equipped with one side port, was inserted into the truncus arteriosis and secured with two ligatures (Stiffler et al 1983). The incisions were sutured closed and additional sutures were used to anchor the cannula to the mandible.…”
Section: Surgerymentioning
confidence: 99%
“…Most animals investigated in this manner respond to the respiratory acidosis with a compensatory metabolic alkalosis (Toews and MacIntyre 1978;Boutilier et al 1979;Boutilier and Toews 1981;Stiffler et al 1983) which is qualitatively similar to the mammalian response (Davenport 1974) but generally less complete. A few amphibians do not show such compensation; however, such species appear to be unable to augment cutaneous bicarbonate uptake and generation (Stiffler et al 1983) or to curtail urinary -cutaneous bicarbonate loss (Heisler et al 1982). Amphibian respiratory responses to metabolic acid -base disturbances are much less clearly understood.…”
Section: Introductionmentioning
confidence: 99%